The Effect of Applying Canva On Students’ Achievement in Writing Descriptive Text at The Tenth Grade Smk PAB I Helvetia Academic Year 2023-2024 - Siregar, Fitriani; Rangkuti, Linda Astuti; Harahap, Yunita Mutiara (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The objective of this research is to investigate if applying Canva significantly affects students’ achievement in writing descriptive text. This research was conducted by using experimental research design. The population of this study was the tenth grade of SMK Swasta PAB 1 Helvetia which has two parallel classes namely X-Titl 1 and X-Titl 2. Each class consisted of 15 students. So, the total number of population was 30 students. Cluster random sampling with Spin the Wheel Technique was employed in selecting the sample. The class X-Titl 2 was selected as experimental group and the class X-Titl 1 was selected as control group. The experimental group was taught by applying Canva while the control group was taught without applying Canva. The instrument used in this research was writing test. The data were analyzed by using t-test. After the data were calculated, it was found that tobserved was higher than ttable (3.80 >2.00) with the degree of freedom df =58 at the level of significance α =0.05. It meant that Ha was accepted and Ho was successfully rejected. Thus, applying Canva significantly affects students’ achievement in writing descriptive text.